A TWO-WAREHOUSE INVENTORY MODEL WITH REWORK PROCESS AND TIME-VARYING DEMAND - Nurhasril, Nurnadiah; Supadi, Dr. Siti Suzlin; Omar, Prof. Dr. Mohd (Malaysian Journal of Science, 2023)
A two-warehouse inventory model with deteriorating items and rework process with time varying demand rate is presented. The Last-In-First-Out (LIFO) and First-In-First-Out (FIFO) policies are considered with the assumption that the holding cost is higher in the rented warehouse (RW) compared to the owned warehouse (OW). The aim of the proposed model is to determine the optimum values of time in a production cycle that will minimise the total relevant cost, TRC*. We have utilised Microsoft Excel Solver as a solution tool, in which the generalised reduced gradient (GRG Nonlinear) method has been chosen as the solving method. The result is further verified using the built-in function in the Mathematica software. We observed that given same changes are made to the parameters in both the LIFO and FIFO systems, a lower total relevant cost, TRC* is obtained in the LIFO system. This shall mean that the LIFO system is less expensive than the FIFO system, provided that the holding cost in RW is higher than the holding cost in OW. The flow of inventory in the LIFO system suggests that items stored last in the owned warehouse will be dispatched first. This is an important factor for manufacturers in ensuring that items are distributed at optimal freshness.